Gene Controlling High Milk Lactoferrin Content in Holstein Friesian Cows - Cece Sumantri (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
Lactoferrin is considered as an antimicrobial and antiviral protein, therefore milk that contains high lactoferrin is potential for health-enhancing nutraceuticals for food and pharmaceutical applications . The main objective of this paper is to discuss in more detail about lactoferrin function and how gene could control high lactoferrin content in milk . Milk lactoferrin content is still various among individual . Therefore, selection should be carried out to increase lactoferrin content in local Friesian Holstein . The selection could be accelerated by using lactoferrin gene as a gene marker that directly contributes to the milk lactoferrin content . Key words : Lactoferrin, antimicrobial, antiviral, selection, gene marker